Effects of Magnoliae Flos on Atopic Dermatitis-Like Inflammation Evaluated via Extracellular Signal-regulated Kinase or Signal Transducers and Activators of Transcription 1/3 Signalling Pathways - Tae-Young Gil; Bo-Ram Jin; Yea-Jin Park; Hye-Min Kim; Hyo-Jin An (Medical Journals Sweden, 2023)
Atopic dermatitis is a chronic inflammatory skin  disease. Skin is the largest organ and plays a pivotal role in protecting the body. Not only does the skin act as a physical barrier against the external environment, but it also has its own immune system. Atopic dermatitis is caused by prolonged excessive inflammatory responses that worsen under imbalanced cutaneous immune system skin conditions. Although the prevalence and burden of atopic dermatitis is increasing, the standard therapeutic agents remain unclear due to  the complicated pathophysiology of the condition. The objective of this study is to examine the use of Magnoliae flos, the dried flower bud of Magnolia biondii or  related plants. The effects and underlying mechanism of  action of aqueous extract of the buds of Magnoliae flos (MF) were evaluated. Immortalized human keratinocytes (HaCaT) stimulated with tumour necrosis factor-α and interferon-γ mixture and NC/Nga mice stimulated with 2,4-dinitrochlorobenzene were used as atopic dermatitis models, in vitro and in vivo, respectively. The effects of MF were determined by measuring the suppression of pro-inflammatory signalling pathways, such as extracellular signal-regulated kinase or signal transducers and activators of transcription 1/3 and restoring skin barrier molecules. In conclusion, MF is a potential therapeutic alternative for the treatment of atopic dermatitis through repressing inflammatory pathways.